STRATEGI PENGUATAN KAPASITAS BIROKRASI PEMERINTAH DAERAH KOTA MAKASSAR PASCA PANDEMI COVID-19 - Nur Nisa Nila Wardani S.; Nuryanti Mustari; Sulastri Sulastri; Sulfiyanti Sulfiyanti; Ulfiah Syukri (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2022)
ABSTRACT The Covid-19 pandemic has spread throughout the world, including Indonesia, due to the influence of globalization supported by advances in information and communication technology. The globalization of Covid-19 has had an impact on people's lives, the private business world, and government. The impact of the Covid-19 pandemic, especially for the Regional Government Bureaucracy, is the emergence of problems with weaknesses in the institutional aspects and behavior of the bureaucratic apparatus. However, there are also challenges and opportunities that can be utilized properly in policy making to overcome problems that arise after the pandemic. In this context, the handling of the pandemic can be handled properly if it is supported by good governance and digital bureaucracy. The institutional reform approach and the behavior of the local government bureaucracy will be good. The local government's institutional reform approach, both improvement of organizational forms and missions, regulations (policies), procedures, methods, and working mechanisms of public services will enable the local government bureaucracy to carry out its duties properly in overcoming the pandemic. Reforms through improving the behavior of the bureaucratic apparatus (ASN) both through education and training, remuneration policies, career development or others will make the local government bureaucracy able to carry out public services well after the Covid-19 pandemic. Keywords: The Covid-19 Pandemic, Local Government Bureaucracy, Bureaucratic Reform, Globalization, and Good Governance.